2011
DOI: 10.1111/j.1439-0272.2011.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Butyl paraben-induced changes in DNA methylation in rat epididymal spermatozoa

Abstract: Parabens have been shown to affect male rodent reproductive parameters, including testosterone levels and sperm production. In this study, we examined the effect of long-term exposure to butyl paraben (BP) on rat epididymal sperm DNA methylation. Adult male rats were exposed to BP (0, 10, 100 and 1000 mg kg(-1) per day) according to OECD TG407 for a repeated 28-day oral toxicity study. Sperm DNA methylation was examined by differential display random amplification of polymorphic DNA (RAPD) following methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 28 publications
0
29
0
2
Order By: Relevance
“…Parabens have weak estrogenic activity [56] and can induce proliferation of breast cancer cells [13]. In male rodents, butyl or propyl paraben exposure decreased sperm production, fetal testosterone, and/or epididymal weight [57, 58], and caused epigenetic changes in sperm [59]. …”
Section: Discussionmentioning
confidence: 99%
“…Parabens have weak estrogenic activity [56] and can induce proliferation of breast cancer cells [13]. In male rodents, butyl or propyl paraben exposure decreased sperm production, fetal testosterone, and/or epididymal weight [57, 58], and caused epigenetic changes in sperm [59]. …”
Section: Discussionmentioning
confidence: 99%
“…In the study of Stouder et al [111] alcohol administration in pregnant mice induced hypomethylation of H19 imprinted gene and may have contributed to the decreased spermatogenesis. In another study [112], Park et al have shown that long-term exposure to butyl paraben (BP) can cause DNA hypermethylation from the mitotic through post-meiotic stage in adult rat testes.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Higher paraben levels have been associated with reduced methylation at DMR2 of IGF2 in human placental tissue [75]. In the rat, postnatal exposure to butylparaben was shown to alter DNA methylation in sperm from F0 males, but no breeding was conducted to investigate transmission of an altered phenotype [92]. In an in vitro study, Pugazhendhi et al (2007) observed upregulation of MLL2 upon paraben treatment in MCF-7 cells [93].…”
Section: Bpa Phthalates and Parabens: Modes And Mechanisms Of Acmentioning
confidence: 99%